An investigation into the Impact of Operational Readiness Factors on the Success of Airports Projects in the UAE - Al-Mazrouie, Jumah Rashid (2017)
In traditional project management literature, we notice the absence of a dedicated phase for operations and maintenance preparation and support for the newly completed product. Consultants, contractors and project managers do not interfere with the operation phase or with how the project will run after completion, as their contractual scope is to deliver the project on time, on schedule and within budget. Operational problems may appear once the project is set for operations and these problems could be the results of mistakes that were made during the project life-cycle phases, which were not picked up during the commissioning phase of the project. Scholars in the literature further argue that in the initial phase of operations, problems may start to surface that result in a decline or low level of performance vis-à-vis the services provided, which results in a reputational and financial impact on the project’s owner and other operational stakeholders. This study explores the factors that impact upon the operational readiness success of com-plex multi-stakeholder airport projects. The study uses mixed methods (triangulation), comprising firstly a focus group categorisation assessment of operational readiness fac-tors based on a study of the existing literature (enabling the design of a survey instrument). Emergent from this process were four readiness factors with 68 operational readiness items. To support the study, the Delphi method was employed for categorisation assess-ment of operational readiness. The second step of the methodology was to conduct a sur-vey among 900 airport stakeholders and project managers working across four interna-tional airports based in the United Arab Emirates (Dubai International Airport, Al-Mak-toum International Airport-Dubai, Abu Dhabi International Airport and Sharjah Interna-tional Airport). Statistical tools of SPSS/AMOS are employed to analyse the quantitative data collected from the questionnaire. In particular, statistical analysis was undertaken vi V7.0 Operational Readiness along with Structural Equation Modelling (SEM). The study finds a significant correla-tion between operational readiness and project success. The study also confirms that op-erational readiness is a second order variable consisting of four factors. These were facil-ities readiness, people readiness, technology readiness and organisation readiness. Emergent from the study will be the development of a conceptual framework that can assist operations readiness practitioners to enhance the success of the transition of com-pleted projects to fully operational endeavours, in particular on the first day of operation. The main contribution of the study is the development of the Airport’s operational readi-ness framework and the list of confirmed items that can be used to support operational organizations to prepare for operating new airport’s facilities within UAE. It is also noted that available studies explicitly contextualised within complex multi-stakeholder infra-structure projects (such as in the case of airports) remain sparse. Thus, it is argued that this doctoral study might serve as the basis for much wider empirical studies on the notion of ‘operational readiness’ within the context of operations and more specifically, project management.